Consumer Search in Retail Gasoline Markets1. (27th April 2017) - Byrne, David P.; de Roos, Nicolas
Abstract : This paper develops direct tests for search behavior in retail gasoline markets. We exploit a unique market‐level dataset that allows us to directly measure search intensity with daily web traffic data from a gasoline price reporting website and perfectly measure daily changes in price levels and dispersion. Our simple yet powerful tests provide strong evidence of both cross‐sectional and intertemporal price search.